Capital intelectual e desempenho organizacional na indústria farmacêutica - Peinado, Elaine Sefrian (2016)
This study aims to determine the effect of intellectual capital and its components on business performance in a pharmaceutical manufacturing company. The theoretical framework consists of aspects of the intellectual capital, segregated into human, structural and relational capital, and business performance considered the financial dimensions, internal and process. A single case study was quantitative approach in a pharmaceutical manufacturing company with extensive intellectual capital. Data collection was conducted through a questionnaire and the data were analyzed with descriptive statistics and application of structural equation modeling (Partial Least Square - PLS). The survey results consisted of a structural model with explanatory power of the dependent variable organizational performance of 72.4%. It found a significant direct association between the human and structural capital and between structural capital and relational, and a significant direct association between relational capital and performance and the increase in the explanatory power of the structural model with the inclusion of interactions between components intellectual capital. It follows from these results, the relevance of the company performing the holistic management of intellectual capital, since it is a key element in managing business performance. However, the survey coverage limitations instigate replication of this model in other companies in the same industry for comparison of results.